Comparison of the Aggregate Production Planning for Low-Demand Products in an MTO and MTS Systems Based on Linear Programming in the Ceramic Industry - Paez Gonzalez, D. K. (2018)
The aggregate production planning for low-demand items in a ceramic company is based on a Make-to-order (MTO) policy (no inventories are allowed). The production scheduler receives forecasts for the next 12 months and must develop an updated master production schedule to meet all requirements. Plaster moulds are required to produced finished goods. Due to the lack of mould storage capacity in the plant, after fulfilling demand, the required plaster moulds must be scrapped, incurring in high manufacturing cost. Thus, in this project, a reduction of mould production is proposed through a Make-to-stock (MTS) system, where holding inventory for low-demand items is allowed. A linear programming model is formulated with the objective of minimise total operational costs; mould production costs, inventory costs, setup costs and penalty costs. The model shows an optimal production schedule, and we compare it with the current MTO approach. Despite a significant increase in holding costs is found, the reduction in the remaining costs result in the saving of 7.51% from the total costs. The model allows to meet current market demand forecasts in a short time, but in the case of an unexpected order, the customer will have to be granted a lead time according to the time needed to complete this requirement. For further research, goal programming method can be applied in order to seek more goals to achieve.